2008
DOI: 10.1189/jlb.0108030
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning with high mobility group box 1 (HMGB1) induces lipopolysaccharide (LPS) tolerance

Abstract: High mobility group box protein 1 (HMGB1) modulates the innate immune response when present in the extracellular compartment. Receptors for HMGB1 include TLR4, TLR2, and the receptor for advanced glycation end products (RAGE). We tested the hypothesis that extracellular HMGB1 can induce LPS tolerance. HMGB1 dose-response experiments were performed on IFN-gamma-differentiated human monocyte-like THP-1 cells. Treatment with 1 microg/ml HMGB1 18 h before exposure to LPS (1 microg/ml) decreased TNF release, NF-kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 44 publications
3
57
0
Order By: Relevance
“…Various receptors are known to interact with HSP70 and HMGB1 and, among them, TLR4 and TLR2 seems to be important in mediating HSP70-and HMGB1-induced inflammatory responses (19,20,(32)(33)(34)(35)(36)(37). These receptors are known to respond to HSP70 and HMGB1 only after binding to other molecules (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Various receptors are known to interact with HSP70 and HMGB1 and, among them, TLR4 and TLR2 seems to be important in mediating HSP70-and HMGB1-induced inflammatory responses (19,20,(32)(33)(34)(35)(36)(37). These receptors are known to respond to HSP70 and HMGB1 only after binding to other molecules (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that another endogenous TLR4 agonist, HMGB1, could induce LPS tolerance of monocyte lineage cells in a RAGE-dependent manner. 50 Therefore, there is intersection between RAGE and TLR4 BLOOD, 13 SEPTEMBER 2012 ⅐ VOLUME 120, NUMBER 11 For personal use only. on June 19, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Alternately, it may underscore that the plasma level of HMGB1 is critical for the survival of endotoxemia or sepsis. Although it is difficult to explain how CO inhibits the release HMGB1 at the present time, CO can inhibit nuclear factor-B activity or p38 mitogen-activated protein kinase (Ulloa et al, 2002;Bonaldi et al, 2003;Aneja et al, 2008) or activate peroxisome proliferator-activated receptor-␥ (Hoetzel et al, 2008). Therefore, further study is needed to determine whether possible mechanism(s) of CO exerts on the HMGB1 release by LPS-or CLP-induced sepsis.…”
Section: Co Inhibits Hmgb1 Release In Lps-and Clp-induced Sepsis 179mentioning
confidence: 99%